Serum Irisin as a Potential Biomarker for Cognitive Decline in Vascular Dementia - Zhang, Feng; Hou, Guangshun; Hou, Guangjian; Wang, Congan; Shi, Bin; Zheng, Yuekun (Frontiers in Neurology, 2021)
Background: Irisin, a new exercise-related myokine, has been shown to be associated with a variety of diseases including serious neurological disorders. However, whether irisin is involved in the pathogenesis of vascular dementia (VD) has not yet been reported. Our aim is to determine the serum irisin level in patients with VD and investigate its relationship with cognitive function. Methods: The subjects of the study were VD patients and controls with normal cognitive function who were hospitalized in the Neck-Shoulder and Lumbocrural Pain Hospital of Shandong First Medical University from July 2018 to June 2020. Upon admission, a cognitive function assessment was performed. Enzyme-linked immunosorbent assay (ELISA) was used to determine the concentration of irisin in serum. Results: During the study period, 187 subjects (82 controls and 105 VD patients) were included in the analysis. The serum irisin level of VD patients was significantly lower than that of the control group (p < 0.001). Spearman analysis showed that irisin was positively correlated with HLD-C and MoCA, and negatively correlated with all clinical characteristics except for HCY. Logistic regression analysis showed that after adjusting for all clinical characteristics, the serum irisin of VD patients still had a significant correlation with MoCA (β = 0.304, p = 0.029). According to receiver operating characteristic (ROC) curve analysis, the diagnostic accuracy for serum irisin levels on VD was 76% with the sensitivity and 71% with specificity respectively. Conclusions: These data indicate that a decrease in serum irisin levels is a powerful biological marker for cognitive decline in patients with VD, even after adjustment for risk factors. Further multi-center studies need to confirm this connection, which may pave the way for new treatment options.